Architecture of the ATG2B-WDR45 complex and an aromatic Y/HF motif crucial for complex formation. Issue 11 (2nd November 2017) - Zheng, Jing-Xiang; Li, Yan; Ding, Yue-He; Liu, Jun-Jie; Zhang, Mei-Jun; Dong, Meng-Qiu; Wang, Hong-Wei; Yu, Li
ABSTRACT: PtdIns3P signaling is critical for dynamic membrane remodeling during autophagosome formation. Proteins in the Atg18/WIPI family are PtdIns3P-binding effectors which can form complexes with proteins in the Atg2 family, and both families are essential for macroautophagy/autophagy. However, little is known about the biophysical properties and biological functions of the Atg2-Atg18/WIPI complex as a whole. Here, we demonstrate that an ortholog of yeast Atg18, mammalian WDR45/WIPI4 has a stronger binding capacity for mammalian ATG2A or ATG2B than the other 3 WIPIs. We purified the full-length Rattus norvegicus ATG2B and found that it could bind to liposomes independently of PtdIns3P or WDR45. We also purified the ATG2B-WDR45 complex and then performed 3-dimensional reconstruction of the complex by single-particle electron microscopy, which revealed a club-shaped heterodimer with an approximate length of 22 nm. Furthermore, we performed cross-linking mass spectrometry and identified a set of highly cross-linked intermolecular and intramolecular lysine pairs. Finally, based on the cross-linking data followed by bioinformatics and mutagenesis analysis, we determined the conserved aromatic H/YF motif in the C terminus of ATG2A and ATG2B that is crucial for complex formation.